What science is and how it works - Derry, Gregory Neil, 1952- (Princeton University Press, 1999)
How does a scientist go about solving problems? How do scientific discoveries happen? Why are cold fusion and parapsychology different from mainstream science? What is a scientific worldview? In this lively and wide-ranging book, Gregory Derry talks about these and other questions as he introduces the reader to the process of scientific thinking. From the discovery of X rays and semiconductors to the argument for continental drift to the invention of the smallpox vaccine, scientific work has proceeded through honest observation, critical reasoning, and sometimes just plain luck. Derry start.